SLC22A2 variants and dolutegravir levels correlate with psychiatric symptoms in persons with HIV. (14th December 2018) - Borghetti, A; Calcagno, A; Lombardi, F; Cusato, J; Belmonti, S; D'Avolio, A; Ciccarelli, N; La Monica, S; Colafigli, M; Delle Donne, V; De Marco, R; Tamburrini, E; et al.
Abstract: Background: Neuropsychiatric symptoms (NPs) have been reported with dolutegravir use. We hypothesized that increasing dolutegravir trough concentrations ( C trough ) and/or polymorphism in the SLC22A2 gene, encoding the organic cation transporter-2 (OCT2), which is involved in monoamine clearance in the CNS and is inhibited by dolutegravir, might be associated with NPs. Methods: A cross-sectional cohort of HIV-positive patients treated with a dolutegravir-containing regimen underwent determination of allelic discrimination for SLC22A2 808 C → A polymorphism and dolutegravir C trough . The Symptom Checklist-90-R [investigating 10 psychiatric dimensions and reporting a general severity index (GSI)], a self-reported questionnaire and the Mini-International Neuropsychiatric Interview were offered to investigate current NPs. The effects of dolutegravir C trough and the SLC22A2 gene variant on NPs were explored by multivariable logistic regression. Results: A cohort of 203 patients was analysed: 71.4% were male, with median age 51 years and 11 years of ART exposure. Median time on dolutegravir was 18 months. Dolutegravir was associated with different antiretroviral combinations (mainly lamivudine, 38.9%, and abacavir/lamivudine, 35.5%). SLC22A2 CA genotype was independently associated with an abnormal GSI [adjusted OR (aOR) 2.43; P = 0.072], anxiety (aOR 2.61; P = 0.044), hostility (aOR 3.76; P = 0.012) and with moderate to severe headache (aOR 5.55; P = 0.037), and dolutegravir C trough was associated with hostility (fourth versus first quartile aOR 6.70; P = 0.007) and psychoticism (fourth versus first quartile aOR 19.01; P = 0.008). Other NPs were not associated with SLC22A2 polymorphism or dolutegravir C trough . Conclusions: A variant of the OCT2-encoding gene, in addition to or in synergy with higher dolutegravir C trough, is associated with a set of NPs observed during dolutegravir therapy.